STUDI MORFOMETRIK IKAN GABUS (Channa striata) DI RAWA GENANGAN BANJIR AIR GEMURUH KECAMATAN BATIN III KABUPATEN BUNGO PROVINSI JAMBI - Dahlia Dahlia; Syafrialdi Syafrialdi; Muhammad Natsir Kholis (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
The aim of the study was to determine the morphometrics of snakehead fish. The implementation was carried out in August – September 2021. Fish sampling was carried out in a flooded swamp in Air Gemuruh Village, Bungo Regency, Jambi Province. The experimental fishing method was chosen for data collection. The data analysis used is descriptive analysis and Cluster Analysis Hierarchy (CAH) analysis. The morphometrics tested were only seven characters and were compared based on gender. The results showed that morphometric male and female snakehead fish could be divided into three groups of close relationship between morphometric characters. The first group had a very similar close relationship, consisting of the characters of Mouth Opening (BM), Tail Length (PE), Body Width (LB) and Head Length (PK). The second group had a fairly similar close relationship, consisting of dorsal fin length (PSG) and fin length (PS). While the last group has a close relationship that is less similar, namely Total Length (PT). The closeness of these characters is suspected from the size (range) between characters that have a significant difference.